Moisture damage of aggregate-bitumen bonds - Zhang, Jizhe (2016)
Moisture damage of the asphalt mixture is defined as the loss of strength, stiffness and durability due to the presence of moisture (in a liquid or vapour state) leading to adhesive failure at the aggregate-bitumen interface and/or the cohesive failure within the bitumen or bitumen-filler mastic. The presence of moisture can accelerate the distress of asphalt pavement in several different modes, such as rutting, fatigue cracking, thermal cracking and the formation of potholes. In the field, the moisture damage normally happens first at the interface of two pavement layers or at the bottom of pavement layers and develops gradually upward. Once moisture has come into contact and interacted with the asphalt mixture, moisture damage could be developed by the following mechanisms: detachment, displacement, spontaneous emulsification, pore pressure, and hydraulic scour. It should be mentioned that moisture damage is not limited to only one mechanism but is the result of a combination of several mechanisms.